2021
DOI: 10.1111/ijcp.14156
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of rubella virus among pregnant women: A 4‐year registered‐based study from family medicine and obstetric clinics in Saudi Arabia

Abstract: Objectives This study aimed to determine rubella virus infectivity and immune status in pregnant females who visited the family medicine and obstetrics clinics at a large hospital in Saudi Arabia, and to identify the possible predictors of rubella susceptibility. Methods This registered‐based, cross‐sectional study included pregnant, aged between 18 and 50 years old, who presented for the first antenatal visit between 2017 and 2020. Data on sociodemographic, antenatal characteristics and serological results we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…22 In 2020, one study in western part of Saudi Arabia showed that 88.9% of women are immune to rubella and another study showed that rubella susceptibility in women was as high as 24%. 23 , 24 Furthermore, WHO report 62 rubella cases in Saudi Arabia in 2019 along with 4 cases of congenital rubella syndrome in the period 2017–2018. 22 Therefore this study was done to determine the seroprevalence of rubella in the eastern province of Saudi Arabia and report cases of acute rubella infections to guide and assess national vaccination programs.…”
Section: Discussionmentioning
confidence: 99%
“…22 In 2020, one study in western part of Saudi Arabia showed that 88.9% of women are immune to rubella and another study showed that rubella susceptibility in women was as high as 24%. 23 , 24 Furthermore, WHO report 62 rubella cases in Saudi Arabia in 2019 along with 4 cases of congenital rubella syndrome in the period 2017–2018. 22 Therefore this study was done to determine the seroprevalence of rubella in the eastern province of Saudi Arabia and report cases of acute rubella infections to guide and assess national vaccination programs.…”
Section: Discussionmentioning
confidence: 99%
“…Jonas et al reported in a survey of women of reproductive age in Namibia that rubella antibody seroprevalence was higher in urban residents than in rural residents [ 19 ]. AlShamlan et al reported in a survey of pregnant women in Saudi Arabia that rubella antibody seroprevalence decreases with increasing age [ 20 ]. Liu et al reported in a survey of women preparing for pregnancy in rural China that women in regions with the low gross domestic product (GDP) per capita were more likely to be susceptible to rubella than women in regions with high GDP per capita [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rubella is caused by the rubella virus, an enveloped, single-stranded, positive-sense Paramyxo-virus R.N.A. virus that is the only member of the genus Rubivirus [5] . Rubella is usually a mild disease that subsides on its own.…”
Section: Introductionmentioning
confidence: 99%